Non-Agricultural Economic Functions of Rural Areas in the Łódzkie Voivodship (1999–2009) - Marcin Wójcik (Barometr Regionalny)
This article addresses the issue of functional development of rural areas in the Łódzkie Voivodship. Empirical research was preceded by a description of directions in the functional research of rural areas. There are two methods of functional research in geographical studies of rural areas. The first tradition has developed on the basis of settlement geography, while the second lies within the area of agricultural geography where the efforts were concentrated on identification of the functional structure of rural areas. Functional research operating within the concept of a rural area as a multifunctional space differs considerably from the concepts based on the theory of a settlement network or a system concept. In the concept of multifunctional areas, a function is a certain quality of this area, whereas in the theory of a settlement network a function is understood as an activity which describes the rank of a settlement and its relation to other settlements. The article attempts to identify functions of rural areas within the framework of a system concept. In settlement geography functional studies include primarily a description of the settlement structure by the means of depicting a place and explaining the meaning of certain elements within the whole (i.e., in the settlement system). In the research, functions of rural areas are identified within the scope of the functional whole, which in turn is a commune’s settlement network. Indirect methods of dividing the functions of this entity into those endogenous and those exogenous simultaneously describe their local (endogenous) and specialised (exogenous) meanings. The results of the research, and the conclusions drawn, prove that the methods of direct measurement of economic base complements, within the concept of multifunctional space, rural studies very well. The division of employment into exogenous and endogenous and identification of its areas of concentration provides a way to illustrate the rate of a commune's economic openness, and therefore, the connection with other settlement systems. Among the most important conclusions emerging from the results of the research the following should be noted. There is a systematic growth of the importance of non-agricultural functions in the rural areas of the Łódzkie Voivodship (1999–2009). The most important system-forming element among non-agricultural functions is manufacturing, trade and transportation. Non-agricultural functions are characterised by relatively high spatial concentration, especially in the Łódź Agglomeration and in the suburban zones of medium towns.